Relationship between the timing of relapse and plasma drug levels following discontinuation of cariprazine treatment in patients with schizophrenia: indirect comparison with other second-generation antipsychotics after treatment discontinuation - Correll CU (Dove Medical Press, 2019)
Christoph U Correll,1–3 Rakesh Jain,4 Jonathan M Meyer,5 Antonia Periclou,6 Timothy Carrothers,6 Ágota Barabássy,7 Mehul Patel,8 Willie Earley91Department of Psychiatry, Northwell Health, The Zucker Hillside Hospital, Glen Oaks, NY, USA; 2Hofstra Northwell School of Medicine, Department of Psychiatry and Molecular Medicine, Hempstead, NY, USA; 3Charité Universitätsmedizin, Department of Child and Adolescent Psychiatry, Berlin, Germany; 4Texas Tech University School of Medicine – Permian Basin, Department of Psychiatry, Midland, TX, USA; 5University of California, San Diego School of Medicine, Department of Psychiatry, La Jolla, CA, USA; 6Allergan, Department of Clinical Pharmacology, Madison, NJ, USA; 7Department of Medical Affairs, Gedeon Richter Plc, Budapest, Hungary; 8Department of Medical Affairs, Allergan, Madison, NJ, USA; 9Department of Clinical Development, Allergan, Madison, NJ, USACorrespondence: Christoph U CorrellThe Zucker Hillside Hospital, Psychiatry Research, 75-59 263rd Street, Glen Oaks, NY 11004, USATel +1 718 470 4812Email ccorrell@northwell.eduObjective: To explore the timing of relapse following drug discontinuation and its relationship to estimated plasma levels and elimination half-life by comparing data from a randomized, placebo-controlled discontinuation study of cariprazine with those from similarly designed and conducted randomized control trials of other oral atypical antipsychotics (AAPs).Methods: Data from a long-term, randomized, double-blind, placebo-controlled relapse prevention study in participants with schizophrenia (NCT01412060) were analyzed. Similarly designed, published studies of other AAPs were used for comparison. Time to drug-placebo relapse separation and relapse rates were estimated from Kaplan–Meier curves and evaluated descriptively. Separation was defined as a sustained difference of ≥5% incidence of relapse between the AAP and placebo curves.Results: The Kaplan–Meier curve for cariprazine showed a time to drug-placebo relapse separation at 6–7 weeks after randomization, compared to the Kaplan–Meier curves for the other AAPs, which showed earlier separation at 1–4 weeks. The placebo relapse rates at 4 weeks after randomization were 5% for cariprazine and 8–34% for other AAPs. Geometric mean values of model-predicted plasma concentrations for total active cariprazine moieties (sum of cariprazine, desmethyl-cariprazine, and didesmethyl-cariprazine) were 20.0 and 6.1 nM at 2 and 4 weeks after discontinuation, respectively. Elimination half-lives of other AAPs and their active metabolites (<4 days) suggest that plasma concentrations would be low or negligible at 2–4 weeks after last dose.Conclusion: Discontinuation of cariprazine treatment appeared to be associated with a delayed incidence of relapse compared with other AAPs, which may be due to the longer half-life of cariprazine and its active metabolites.Keywords: cariprazine, schizophrenia, half-life, occupancy